Health Financing Revisited : A Practitioner's Guide - Gottret, Pablo (Washington, DC: World Bank, 2012)
This overview of health financing tools, policies and trends--with a particular focus on challenges facing developing countries--provides the basis for effective policy-making. Analyzing the current global environment, the book discusses health financing goals in the context of both the underlying health, demographic, social, economic, political and demographic analytics as well as the institutional realities faced by developing countries, and assesses policy options in the context of global evidence, the international aid architecture, cross-sectoral interactions, and countries' macroeconomic frameworks and overall development plans.